A Point Prevalence Survey of Antimicrobial Use at Geita Regional Referral Hospital in North-Western Tanzania - Lutugera Kihwili; Vitus Silago; Emiliana N. Francis; Vicent A. Idahya; Zabron C. Saguda; Siana Mapunjo; Martha F. Mushi; Stephen E. Mshana (MDPI AG, 2023)
We conducted a point prevalence survey (PPS) to determine the prevalence of antibiotic use at Geita Regional Referral Hospital (GRRH) located along the shores of Lake Victoria in north-western Tanzania. This has led to the identification of gaps for improvement. This PPS study was conducted on 9-10 March 2023. Patient-related information, including sociodemographic and clinical data, was collected from medical records. STATA software version 15.0 was used to perform descriptive data analysis. About 94.8% (55/58) patients were on antibiotics with a mean (±SD) prescription of 2 (±0.5) antibiotic agents ranging from 1 to 4 different agents. The commonest indications of the antibiotic prescription were medical prophylaxis 47.3% (26/55) followed by empiric treatment 41.8% (23/55). In total, 110 prescriptions were made, of which metronidazole (25.5%; n = 28), ceftriaxone (23.6%; n = 26), and ampicillin-cloxacillin (23.6%; n = 26) were frequently observed. Only 67.3% (n = 74) of prescriptions complied with Tanzania Standard Treatment Guidelines. Moreover, according to the WHO-AWaRe classification, 50.9%, 23.6%, and 25.5% were under the Access category, Watch category, and Not Recommended category, respectively. The prevalence of antibiotic use among patients admitted to GRRH was high, whereby medical prophylaxis and empiric treatment were the commonest indications for antibiotic prescription. To support rational therapy and antimicrobial stewardship initiatives, we recommend that laboratories in regional hospitals be equipped to conduct sustained routine culture and antimicrobial susceptibility testing.